New country records for three species of frog from Myanmar including two genera (Nasutixalus and Oreolalax) - Rahman, Md Mizanur; Chen, Jin-Min; Wu, Yun-He; Chen, Hong-Man; Lwin, Ye-Htet; Murphy, Robert W.; Li, Guo-Gang; Che, Jing (Zootaxa, 2020)
Myanmar, a biodiversity hotspot, harbors a striking diversity and endemism of species. Despite this, its herpetofauna remains one of the least explored in continental Asia due to restrictions of crossing political boundaries and infrastructure in remote regions. Many species in adjacent China and India are hypothesized to occur in Myanmar but records are wanting. Recent fieldwork found the frogs Polypedates braueri, Nasutixalus jerdonii and Oreolalax jingdongensis there, and the latter two species represent new generic records for Myanmar. All major morphological characters of these populations match the original descriptions. In addition, our matrilineal genealogy based on DNA barcoding confirms their identities. Overall, these findings confirm that the amphibian diversity is underestimated and this has important implications for conservation. Analyses indicate that northern Myanmar is a biogeographic corridor for the Himalayas, southern China, and northeastern India.